KARAKTERISTIK SIFAT FISIK TANAH DAN C-ORGANIK PADA PENGGUNAAN LAHAN BERBEDA DI KAWASAN UB FOREST - Renaldy Christian Siahaan; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
UB forest area has various land uses, namely the use of agroforestry land based on coffee and seasonal crops. This will result in various physical properties of the soil in each use, therefore this study aims to determine the physical properties of the soil in different land uses and obtain optimal land use in the UB Forest area. The research was conducted from June to September 2020 in Malang district. The study was conducted on land use of pine forest areas, pine agroforestry + coffee, pine agroforestry + seasonal crops, mahogany agroforestry + coffee and mahogany agroforestry + seasonal crops. The parameters observed included analyzing bulk density, particle density, porosity, available water, water content pF 2.5 and 4.2, hydraulic conductivity, aggregate stability, texture and organic-C. The results showed that land use in the forest area of UB affected the physical soil, namely bulk density, particle density, porosity, hydraulic conductivity, and aggregate stability. Other physical properties, namely soil texture in the UB area. Dominant forest with dusty and clayey clay textures while available water had no significant effect and pine land use is optimal use based on physical properties of soil density, density, aggregate stability and hydraulic conductivity and is supported by the value of organic-C. Soil organic matter in coffee pine land use also has the highest value than other land ranges from 3.44 to 5.07%